Pengaruh Literasi Keuangan, Persepsi Risiko, dan Locus of Control Terhadap Keputusan Investasi Pengusaha Muda di Singaraja - Febri Mahwan; Nyoman Trisna Herawati (Universitas Pendidikan Ganesha, 2021)
The aspect of perceived behavioral control in theory of planned behavior states that there are support and obstacles factor in everyone to form certain behaviors or actions. This study aims to analyze how much influence financial literacy, risk perception, and locus of control have on the investment decisions of young entrepreneurs in the capital market. This study was conducted with a quantitative approach. The population in this study were young entrepreneurs who are members of the HIPMI (Indonesian Young Entrepreneurs Association) Buleleng Regency and WMS (Singaraja Young Entrepreneurs) organizations and the number of samples in this study were 50 respondents. This study was used purposive sampling technique. The data used are primary data sourced from distributed questionnaires via google form. The technique of data analysis in this study used multiple regression test and data were processed by using software IBM SPS Statistics for windows version 25. The results of this study showed that the variable of financial literacy, risk perception, and locus of control had a significant positive effect toward investment decisions of young entrepreneurs in the capital market.